2017
DOI: 10.1111/tbj.12772
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Insulin Resistance, Metabolic Syndrome, and Type 2 Diabetes in Canadian Women at High Risk for Breast Cancer

Abstract: There is considerable literature on the surveillance and management of women at high risk for developing breast cancer (BC) due to genetic mutations, family history, and mantle radiotherapy at a young age or a high score on risk calculation models (1). These women may benefit from more effective risk management interventions and heightened screening (1). Many of the afore-mentioned BC risk factors are nonmodifiable and it is therefore desirable to identify potential modifiable risk factors and related preventi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 10 publications
0
11
0
Order By: Relevance
“…While our study provides first evidence for a role of resistin in cancer chemoresistance, its role in insulin resistance is well characterized [44]. Incidentally, insulin resistance is also associated with high risk of human cancers [45], including BC [46]. …”
Section: Discussionmentioning
confidence: 99%
“…While our study provides first evidence for a role of resistin in cancer chemoresistance, its role in insulin resistance is well characterized [44]. Incidentally, insulin resistance is also associated with high risk of human cancers [45], including BC [46]. …”
Section: Discussionmentioning
confidence: 99%
“…Many modifiable risk factors for BCa diagnosis have been observed such as smoking and use of oral contraceptives (2) (3) (4) . Metabolic factors such as hypertension, high blood glucose and abdominal obesity are also linked with higher BCa risk and impaired prognosis (5) (6), whereas physical exercise may decrease risk of BCa death (7). Hypertension is very common among breast cancer patients (8).…”
Section: Introductionmentioning
confidence: 99%
“…Women at high genetic risk of BC have an elevated prevalence of IRm and metabolic syndrome [ 14 ]. Observational data indicated that central obesity and high body weight are associated with a greater risk of BC [ 15 ] in women from high-risk families than in women with no family history of BC.…”
Section: Introductionmentioning
confidence: 99%